Stinging Nettle (Urtica dioica) Roots: The Power Underground—A Review - Françoise Martz; Santeri Kankaanpää (Plants)
Stinging nettle (Urtica dioica) is an herbaceous perennial plant native to Eurasia, wildly distributed throughout the temperate parts of the world. Although generally considered as a weed due to its fast growth and invasive capacity, stinging nettle is well suited to cultivation and is currently experiencing a revival as a beneficial crop due to its numerous potential applications. This interest reflects in an increasing number of scientific articles related to nettle in the last years. However, reports mostly focus on the aerial parts of the plant. Roots are rich in numerous phytochemicals such as phytosterols, lignans, coumarins, sugars, and lectins. By compiling the most relevant publications, the aim of this review is to gather the current knowledge about nettle roots, such as root system functioning, biochemical composition, and related functional activities. A special emphasis is placed on lectins (or UDA for Urtica dioica agglutinin) due to their functional activities. This review highlights the potential of nettle root as a source of biomolecules. Gaps of knowledge and possible future directions for nettle root research, production, and uses are discussed.